Pengaruh Literasi Keuangan Syariah, Persepsi Imbal Hasil, dan Motivasi terhadap Minat Investasi di Pasar Modal Syariah - Vania Evanita Puspitasari; Fitri Yetty; Siwi Nugraheni (Journal of Islamic Economics and Finance Studies, 2021)
AbstractThe increase in the number of Indonesians Muslim population, sharia shares and the growth of sharia capital market assets are inversely proportional to the level of Islamic financial literacy and the Islamic capital market of the Indonesian population which is still very low than conventional based on the 2019 National Survey of Financial Literacy and Inclusion. This research aims to investigate the influence of Islamic financial literacy, perception of return, and motivation on investment interest in the Islamic capital market. The research method is quantitative with a sample of 150 Jabodetabek people who know about the Islamic capital market. Data was collected by questionnaire through google form. Analysis of the data used is multiple linear regression using SPSS version 25. The results of the research found that simultaneously there is an influence between Islamic financial literacy, perception of return, and motivation on investment interest. Partially, perception of return and motivation have a positive and significant effect, while Islamic financial literacy has no effect on investment interest. The results of the coefficient of determination test explained that the three independent variables influenced investment interest as much as 22%, the remaining 78% was the influence of independent variables outside the modelAbstrak Peningkatan jumlah penduduk muslim Indonesia dan jumlah saham syariah serta pertumbuhan aset pasar modal syariah berbanding terbalik dengan tingkat literasi keuangan syariah dan pasar modal syariah penduduk Indonesia yang masih sangat rendah daripada konvensional berdasarkan Survei Nasional Literasi dan Inklusi Keuangan tahun 2019. Kajian ini bertujuan untuk mengetahui pengaruh literasi keuangan syariah, persepsi imbal hasil, dan motivasi pada minat investasi di pasar modal syariah. Metode penelitian adalah kuantitatif dengan sampel 150 masyarakat Jabodetabek yang mengetahui tentang pasar modal syariah. Data dikumpulkan dengan kuesioner melalui google form. Analisis data yang digunakan yaitu regresi linier berganda menggunakan SPSS versi 25. Hasil kajian ditemukan bahwasanya secara simultan terdapat pengaruh antara literasi keuangan syariah, persepsi imbal hasil, dan motivasi pada minat investasi. Secara parsial, persepsi imbal hasil dan motivasi berpengaruh positif dan signifikan, sedangkan literasi keuangan syariah tidak berpengaruh pada minat investasi. Hasil uji koefisien determinasi dijelaskan bahwa ketiga variabel independent memengaruhi minat investasi sebanyak 22%, 78% sisanya merupakan pengaruh variabel independent di luar model.